Evaluation of Physical and Thermal Comfort Properties of Copper/Alginate Treated Wool Fabrics by Using Ultrasonic Energy - (:unkn) unknown (Nova Science Publishers, Inc., 2014)
The aim of this study is to treat wool fibre based woven fabric with sodium alginate and copper sulphate by using ultrasonic energy, and then test and analyse the treated fabric's physical and thermal comfort properties including: tensile properties, abrasion behaviour, flexural rigidity, and thermo physiological properties. The fabrics were immersed in 5%, 10% and 15% w/v copper solution and subsequently the fabric specimens were subjected to 10 min and 20 min ultrasonic energy treatment. The results clearly demonstrated that the wool fabric was successfully treated with the copper and the coated fabrics showed significant changes as compared to their untreated forms. The tensile strength of the treated fabrics was strongly affected by the volume of copper in the solution. The abrasion test was performed for up to 50.000 rubs due to the standard test method and there were no considerable differences between the untreated and the treated fabrics. The treatment lowered the flexural rigidity values. The fabric's thermal conductivities and thermal resistances were increased significantly after the treatment. It was also observed that the conductivity of the fabrics increased gradually. Furthermore, the treated fabrics had lower thermal absorbtivity values. The treated fabrics showed considerably lower water vapour permeability compared to the untreated fabrics. The ultrasonic energy application times did not affect any of the measured fabric properties significantly. © 2014 by Nova Science Publishers, Inc. All rights reserved.
Keywords: Alginate; Copper treatment; Physical properties; Thermal comfort; Ultrasonic energy; Wool fabric